2007
DOI: 10.1115/1.2804096
|View full text |Cite
|
Sign up to set email alerts
|

A Heterogeneous Array of Off-Chip Interconnects for Optimum Mechanical and Electrical Performance

Abstract: Demand for off-chip bandwidth has continued to increase. It is projected by the Semiconductor Industry Association in their International Technology Roadmap for Semiconductors that by the year 2015, the chip-to-substrate area-array input-output interconnects will require a pitch of 80 μm. Compliant off-chip interconnects show great potential to address these needs. G-Helix is a lithography-based electroplated compliant interconnect that can be fabricated at the wafer level. G-Helix interconnects exhibit excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In our previous work [24], we have shown that the compliant G-Helix interconnects provide excellent opportunities for I/O customization based on electrical and mechanical requirements. In that work, it has been shown that employing interconnects with varying geometries across a single die is beneficial for the case of G-Helix interconnects.…”
Section: Integrative Solution For Flex Connectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work [24], we have shown that the compliant G-Helix interconnects provide excellent opportunities for I/O customization based on electrical and mechanical requirements. In that work, it has been shown that employing interconnects with varying geometries across a single die is beneficial for the case of G-Helix interconnects.…”
Section: Integrative Solution For Flex Connectsmentioning
confidence: 99%
“…Other advantages of this technology are as follows: 1) The fabrication process can be integrated into wafer-level fine-pitch batch processing; 2) the compliant interconnects will exert minimal force on the die pads and, therefore, will not crack or delaminate the low-K dielectric material on the die; 3) the interconnects will not require an underfill to accommodate the CTE mismatch between the die and the organic substrate, and as no underfill is used, the interconnects assembled with solder will be easily reworkable; by reflowing the solder, the chip can be removed from the substrate; 4) the interconnects can be fabricated at the wafer level and can therefore be potentially cost effective; also, as the interconnect fabrication uses conventional wafer fabrication infrastructure, there are no additional equipment/infrastructure costs; 5) as the interconnects are fabricated using lithography and electroplating, the interconnect dimensions and shape can be varied across the chip to accommodate the electrical, mechanical, and thermal requirements [24]; and 6) lead-free solder can be employed for the interconnect assembly to substrates, and therefore, the technology is environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…The microflex technique is used to establish electrical contact between the polyimide array and rigid substrate. Mechanically flexible interconnects with a fixed vertical height are widely investigated for flip-chip assembly on rigid substrates [25][26][27][28][29][30]. These interconnects minimize the thermo-mechanical stresses due to the mismatch in coefficients of thermal expansion and compensate for the non-planer surface of the substrate as well as potentially allowing rematable connections.…”
Section: Introductionmentioning
confidence: 99%